Multiscale analysis of instabilities in heterogeneous materials using ANM and multilevel FEM - Nezamabadi, Saeid; Zahrouni, Hamid; Yvonnet, Julien; Potier-Ferry, Michel (European Journal of Computational Mechanics, 2012)
In this study, we propose a numerical technique which combines a perturbation approach (asymptotic numerical method) and a multilevel finite element analysis. This procedure allows dealing with instability phenomena in the context of heterogeneous materials where buckling may occur at both macroscopic and/or microscopic scales. Different constitutive relations are applied and geometrical non-linearity is taken into account at both scales. Numerical examples involving instabilities at both micro and macro levels are presented.